Sexually Dimorphic Effects of Aromatase on Neurobehavioral Responses - Shay, Dusti A.; Vieira-Potter, Victoria J.; Rosenfeld, Cheryl S. (Frontiers in Molecular Neuroscience, 2018)
Aromatase is the enzyme responsible for converting testosterone to estradiol. In mammals, aromatase is expressed in the testes, ovaries, brain, and other tissues. While estrogen is traditionally associated with reproduction and sexual behavior in females, our current understanding broadens this perspective to include such biological functions as metabolism and cognition. It is now well-recognized that aromatase plays a vital lifetime role in brain development and neurobehavioral function in both sexes. Thus, ongoing investigations seek to highlight potentially vital sex differences in the role of aromatase, particularly regarding its centrally mediated effects. To characterize the role of aromatase in mediating such functions, effects of aromatase inhibitor (AI) treatments on humans and animal models have been determined. Aromatase knockout (ArKO) mice that systemically lack the enzyme have also been employed. Humans possessing mutations in the gene encoding aromatase, CYP19, have also provided critical insight into how aromatase affects brain function in a possible sex-dependent manner. A better understanding of how AIs, used to treat breast cancer and other clinical conditions, may detrimentally affect neurobehavioral responses will likely promote development of future therapies to combat these effects. Herein, we will provide a critical review of the current knowledge of sex differences in aromatase regulation of various neurobehavioral functions. Although many species have been used to better understand the functions of aromatase, this review focuses on rodent models and humans. Critical gaps in our present understanding of this area will be considered, and important future research directions will be discussed.